Decision making in healthy participants on the Iowa Gambling Task: new insights from an operant approach - Bull, Peter N.; Tippett, Lynette J.; Addis, Donna Rose (Frontiers in Psychology, 2015)
The Iowa Gambling Task (IGT) has contributed greatly to the study of affective decision making. However, researchers have observed high inter-study and inter-individual variability in IGT performance in healthy participants, and many are classified as impaired using standard criteria. Additionally, while decision-making deficits are often attributed to atypical sensitivity to reward and/or punishment, the IGT lacks an integrated sensitivity measure. Adopting an operant perspective, two experiments were conducted to explore these issues. In Experiment 1, 50 healthy participants completed a 200-trial version of the IGT which otherwise closely emulated Bechara et al.’s (1999) original computer task. Group data for Trials 1-100 closely replicated Bechara et al.’s original findings of high net scores and preferences for advantageous decks, suggesting that implementations that depart significantly from Bechara’s standard IGT contribute to inter-study variability. During Trials 101-200, mean net scores improved significantly and the percentage of participants meeting the “impaired” criterion was halved. An operant-style stability criterion applied to individual data revealed this was likely related to individual differences in learning rate. Experiment 2 used a novel operant card task—the Auckland Card Test (ACT)—to derive quantitative estimates of sensitivity using the generalized matching law. Relative to individuals who mastered the IGT, persistent poor performers on the IGT exhibited significantly lower sensitivity to magnitudes (but not frequencies) of rewards and punishers on the ACT. Overall, our findings demonstrate the utility of operant-style analysis of IGT data and the potential of applying operant concurrent-schedule procedures to the study of human decision making.